Clinical-epidemiological characteristics and knowledge on american tegumentary leishmaniosis in a Carabobo state population. Venezuela - Abdel, Karim (2020)
Of American tegumentary leishmaniasis 1.5 million new cases are registered, it is present in 88 countries, this makes it occupy the sixth place among the major diseases of the world and the second among parasitic diseases only behind malaria, but in Latin America they are The work on knowledge of American tegumentary leishmaniasis as support for health control programs is scarce, but the majority only focus on aspects such as: chemical and biological vector control, reservoir study, seroprevalence in endemic areas, pharmacological treatment and immunotherapy. The objective is to determine the clinical-epidemiological characteristics and knowledge about American tegumentary leishmaniasis. Descriptive study with documentary and field research design, based on the review of the epidemiological record and application of a questionnaire. The majority of those affected are young adults (20-59 years) (66.3%) of the male gender, workers (27.4%) with upper limb injuries (40.5%), generally unique (53.4%) and treated (86.3%). 80% know the disease and 83% know the transmitter, and 38% know the pharmacological treatment. It is concluded that those affected with LTA are mainly men, in economically productive age, workers and farmers, with educational levels not exceeding half diversified, located in relative poverty as socio-economic stratum, with unique skin lesions in exposed regions of the body and pharmacologically treated; that the population knows the natural history of the disease and the transmitter, but they are unaware of aspects of the biology of the insect; and who know and prefer the medical-pharmacological treatment of the medical-scientific system and the public curative service.